2020
DOI: 10.3390/su12114530
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Based Approach for Informing Sustainable Infrastructure Resilience Enhancement and Potential Resilience Implication in Terms of Emergency Service Perspective

Abstract: Infrastructure resilience ascribes into the United Nations’ agenda for sustainable development. The more information supporting infrastructure resilience enhancement, the higher chance that it will be done objectively and effectively, and especially in a sustainable way. In spite of many different approaches and data sources, there is a lack of information that respects the emergency service point of view. The main research objective is to investigate factors determining sustainable infrastructure resilience e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Similarly, resilience is, however, considered as a major element of wider sustainability goals. Accordingly, [100] investigated the five dimensions of resilience (physical resilience, structure and setting resilience, organizational resilience, economic resilience, and legal resilience) and were proposed as a risk-based approach for informing the enhancement of sustainable infrastructure resilience and potential resilience implications from the perspective of emergency services. The study has also found that various researchers viewed organizational resilience using different antecedents or predictors as shown in Table 4.2 below:…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, resilience is, however, considered as a major element of wider sustainability goals. Accordingly, [100] investigated the five dimensions of resilience (physical resilience, structure and setting resilience, organizational resilience, economic resilience, and legal resilience) and were proposed as a risk-based approach for informing the enhancement of sustainable infrastructure resilience and potential resilience implications from the perspective of emergency services. The study has also found that various researchers viewed organizational resilience using different antecedents or predictors as shown in Table 4.2 below:…”
Section: Resultsmentioning
confidence: 99%
“…We state this as very positive from the results reliability point of view. Regardless work experience and fire rescue unit, all responders represent the State Fire Service which plays a primary, executory role in fire rescue in Poland (Gromek and Sobolewski, 2020). Such unique group of experts allowed us to holistically connect two closely related perspectives of fire rescue operations as the officers were gaining a knowledge and practical skills necessary for effective command…”
Section: Study Populationmentioning
confidence: 99%
“…As research has progressed, scholars have obtained a more thorough grasp of infrastructure resilience. They began concentrating on the correlation between two or more infrastructures [24][25][26][27] and used interdependence models to examine them. With the continuous development of intelligent supporting technologies such as big data and IoT technology in recent years, some progress has been made in researching new intelligent infrastructure resilience assessments [28].…”
Section: Introductionmentioning
confidence: 99%